Manjae Oral Tradition: An Anthropolinguistic Study of The Tobanese Community In North Sumatra - Gratia Sialagan; Alemina Br Perangin-angin; Mhd Pujiono (UPT. Pengembangan Bahasa IAIN Zawiyah Cot Kala Langsa, 2025)
Study explores the manjae tradition of the Batak Toba Toba community as a form of oral cultural expression that integrates language, ritual, and social values. Positioned within the framework of anthropolinguistics, the research investigates how customary speech, gestures, and symbolic materials function as performative acts that signify social transition, particularly following marriage. Using a qualitative ethnographic approach, data were collected through participant observation, in-depth interviews, and textual documentation, with analysis guided by Spradley’s ethnographic model and speech act theory. The findings reveal that manjae comprises distinct ritual stages—mamio, core ceremonial activities, and manjalangi—each rich in structured speech and symbolic performance. Expressions such as “Horas ma dihita sasudena” and “Hamuna ma situtupi adatmuna” reflect layered functions of advice, blessing, and identity affirmation. The study highlights how elements like ulos, proxemic arrangements, and kinetic gestures reinforce social legitimacy and cultural continuity. In doing so, this research contributes to the understanding of oral tradition not merely as storytelling, but as a dynamic system of communication and cultural inheritance. It also underscores the urgency of preserving manjae amidst sociocultural change, offering a significant contribution to the fields of linguistic anthropology and cultural heritage studies.